Amyloid β-protein oligomers upregulate the β-secretase, BACE1, through a post-translational mechanism involving its altered subcellular distribution in neurons. Issue 1 (December 2015) - Mamada, Naomi; Tanokashira, Daisuke; Hosaka, Ai; Kametani, Fuyuki; Tamaoka, Akira; Araki, Wataru
Abstract Background β-Site amyloid precursor protein cleaving enzyme 1 (BACE1) is a membrane-bound aspartyl protease that initiates amyloid β-protein (Aβ) generation. Aberrant elevation of BACE1 levels in brains of Alzheimer's disease (AD) patients may involve Aβ. In the present study, we used a neuron culture model system to investigate the effects of Aβ on BACE1 expression as well as the underlying mechanisms. Results Rat primary cortical neurons were treated with relatively low concentrations (2.5 μM) of Aβ42 oligomers (Aβ-O) or fibrils (Aβ-F) for 2–3 days. Aβ-O induced a significant increase in protein levels of BACE1, while Aβ-F only had a marginal effect. Levels of amyloid precursor protein (APP) and the major α-secretase, ADAM10, remained unaltered upon treatment with both types of Aβ. Aβ-O treatment resulted in activation of eIF2α and caspase 3 in a time-dependent manner, with no changes in the endoplasmic reticulum (ER) stress marker, GRP78, indicating that a typical ER stress response is not induced under our experimental conditions. Furthermore, Aβ-O did not affect BACE1 mRNA expression but augmented the levels of exogenous BACE1 expressed via recombinant adenoviruses, indicating regulation of BACE1 protein expression, not at the transcriptional or translational but the post-translational level. Immunocytochemical analysis revealed that Aβ-O causes a significant increase in BACE1 immunoreactivity in neurites (both axons and dendrites), but not soma of neurons; this change appears relevant to the mechanism of Aβ-O-induced BACE1 elevation, which may involve impairment of BACE1 trafficking and degradation. In contrast, Aβ-O had no effect on APP immunoreactivity. Conclusion Our results collectively suggest that Aβ oligomers induce BACE1 elevation via a post-translational mechanism involving its altered subcellular distribution in neurons, which possibly triggers a vicious cycle of Aβ generation, thus contributing to the pathogenetic mechanism of AD.